Effect on β″ Precipitates in 6061Al Alloy by the Addition of 1 wt.% Zn - Singh P.; Kumar N. (My University, 2025)
In the present work, a new Al alloy was developed in billet form by adding the 1 wt.% Zinc in 6061 Al alloy (6061 + 1 wt.%Zn Al alloy) through the stir-casting process and compared with the billet of 6061 Al alloy. Both Al alloys underwent for the three different aging temperatures, i.e., 150 °C, 170 °C and 180 °C. The findings demonstrate that adding 1 wt.% zinc to 6061 Al alloy does not form additional precipitates apart from increasing the number density of β″ precipitates. After the aging treatment, the hardness and tensile strength of 6061 + 1 wt.%Zn Al alloy increased when compared to base 6061 Al alloy. In 6061 + 1 wt.%Zn Al alloy after aging at 180 °C for 10 h maximum strength of 380 MPa, percentage elongation of 13.8% and hardness of 138 HV were achieved. Whereas in base 6061 Al alloy after aging at 180 °C for 8 h maximum strength of 330 MPa, percentage elongation of 13% and hardness of 118 HV were achieved. 6061 + 1 wt.%Zn Al alloy has superior mechanical properties as compared to the base 6061 Al alloy in investigated aging temperature and time. The hardness and strength in 6061 + 1 wt.%Zn Al alloy were increased after aging due to formation of more fraction of needle shape β″-precipiates as compared to 6061 Al alloy. The overall volume fraction of β″-precipiates (needle as well spherical) were increased in 6061 + 1 wt.%Zn Al alloy because of Zn has an affinity for occupying Mg1/Al, Si1, Si2, and Si3/Al sites in the β″ unit cell which increase the volume fraction of β″-precipitates. © ASM International 2025.